Olive cake in the feeding of fattening rabbits : histopathological changes - Rupić, Vlatko (Array, 2020)
Nutritive effect of different levels (10% and 20%) of dried olive cake on the body mass, feed conversion ratio and histopathological changes in tissues in conventionally bred Hyla rabbits was investigated. During a 56-day experimental feeding regime, 60 rabbits were divided into a control group and two experimental groups with 20 animals each (10 males and 10 females). Control group received no olive cake, while the first experimental group received 10% and the second experimental group 20% of dried olive cake throughout the whole feeding period. No significant differences in the body mass were found between the groups in the trial. In both experimental groups, feed conversion was better than in the control group. Histopathological tests were performed on a total of 28 rabbits. Histopathological changes observed in the brain, heart and kidneys of rabbits were the consequence of pathological activity of microsporidian Encephalitozoon cuniculi found in all groups. In the rabbits of both experimental groups fed with olive cake, deposition of fat in the heart, liver, lymph nodes, thyroid gland, adrenal gland and pancreas might be explained by the greater amount of fat from olive oil in the meal. Statistically significant was only the fat deposition in the liver, namely, in hepatocytes. Histopathological screening identified pathological action of fungus Cyniclomyces guttulatus in the digestive tract of all rabbit groups which caused inflammation of the mucous membranes (enteritis) of the entire digestive system (from the stomach to the large intestine) and therefore possibly interfered with the absorption of certain nutrients (vitamins, minerals, etc.).